‘I Haue Ben Crised and Besy’: Illness and Resilience in the Fifteenth-Century Stonor Letters - Thorpe, Deborah (The Mediaeval Journal, 2015)
Abstract The modern and medieval meanings of words reporting ill health often bear little resemblance to one another. This article compares the use of ‘diseased’ and ‘sick’ in the fifteenth-century Stonor family letters. It examines the word ‘crased’, which implies physical ill health most directly, but also suggests emotional, psychological, or spiritual distress in female family members especially. The article then turns to the practical implications of poor health, asking how and why it affected the day-to-day concerns of the Stonors and their associates. It uncovers compelling evidence for resilience in the face of many and competing calls of duty. Finally, the article presents unique palaeographical evidence for the impact of illness, where a correspondent is so ‘seke’ that he can scarcely hold his pen.